The link between English Language Proficiency and Academic Literacy: A scientific explanation - kandagor, Jacqueline; rotumoi, dr. Joseph (Kabarak University, 2016)
language competence in the medium of instruction impacts on academic achievement. Language can either promote or impede the acquisition of knowledge and hence impact on scholastic success Language: crucial means of gaining access to knowledge(Ramapela, 2014) Language for soliciting help, constructing, reformulating and paraphrasing knowledge to one’s own understanding
Keywords: Literacy